Telework:: General Aspects and Characteristics of the Modality in Brazil (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The objective of this article is to analyze telework, presenting its general definition and the characteristics of this modality in Brazil, mainly, in the year 2020. In order to achieve this goal, an approach will be made to the various definitions that telework can receive, in addition to presenting advantages and disadvantages for both the worker and the employer. As for its implementation in Brazil, an analysis was made of the legislation that involves this modality and then an indication of the main disparities found in this modality of work, as well as its effective implementation versus its potential. The deductive approach method and the indirect documentation search technique were used, using doctrinal, scientific and documentary research.Keywords: Telework. Labor Law. CLT. Teleworkers. Potential.